Perancangan Carousel Instagram sebagai Media Edukasi Fibonacci Retracement pada Trading Forex - Desmond Christian Mauwa; Jhon Felix Tubagus (CV. ALIM'SPUBLISHING, 2026)
The development of digital technology has encouraged the use of Instagram as a visual education medium, including for delivering forex trading material. One topic that remains difficult for beginner traders to understand is Fibonacci Retracement, especially in identifying swing high, swing low, entry areas, and price targets. This study aims to design an Instagram carousel as an educational medium for Fibonacci Retracement that is informative, visually appealing, and easy for beginner traders to understand. This research uses the Design Thinking method through five stages: Empathize, Define, Ideate, Prototype, and Test. Data were collected through literature study, observation of trading education content on Instagram, audience needs exploration, and questionnaires distributed to 8 respondents who matched the target users. The findings show that audiences need material that is concise, visual, sequential, and supported by trading chart examples. The carousel prototype received positive responses, as most respondents considered the design attractive, the colors clear, the font readable, the text size appropriate, and the material sequence easy to follow. However, several parts still need improvement, especially entry explanation, swing high, swing low, and target extension. This study implies that Instagram carousel can be an alternative visual education medium to help beginner traders understand Fibonacci Retracement more simply and systematically.